Application of Problem Solving Method and Utilization of Long Single Standard Tools to Increase Learning Math Result of Students IV SDN 03 Merigi Lesson Learning Time 2016/2017 - Suharwati Suharwati (JURIDIKDAS, 2018)
Results of mathematics learning of fourth grade students of SD Negeri 03 Merigi, not as expected or unsatisfactory. There are still many students who value the learning outcomes under the mastery. This is because students have difficulty in solving math problems especially on the subject of measurement (unit of length measurement). Such conditions need to be immediately solved. One effort to overcome this is by using the tool ladder step length measuring and problem solving methods. The problem studied in this research is "Whether through the implementation of problem solving method and using the tool props ladder length measuring unit can improve learning outcomes in completing the questions on the subject of measurement (unit of length measurement) in students of class IV Semester I SD Negeri 03 Merigi, lesson year 2016/2017 The purpose of this classroom action research is to know whether the measurement learning (long unit of measurement) through problem solving method and using the tool ladder step length measure improve the learning outcomes of fourth grade students of SD Negeri 03 Merigi, Kepahiang 2016 / 2017. This classroom action research was conducted in 2 cycles, with research subjects of fourth grade students of SD Negeri 03 Merigi, 2016/2017 as many as 20 students. Each cycle includes the stages of planning, implementation of action, observation and evaluation ends reflection. The results of research that can be presented researchers are as follows. In the first complete cycle studied 12 people and unfinished 10 people with an average of 7.4 or 65% seraf power. While in the second cycle of students who thoroughly studied 20 people and who did not complete 0 people with an average of 89 or 92 percent seraf, because it meets the expected target so the research process is stopped in the second cycle.The conclusion that can be taken is that the problem-solving steps can improve student's learning outcomes in solving the measurement problem (unit of measure length). Therefore, in the study of measurement questions (unit of length measurement) is recommended to use the troubleshooting steps.